Leadership of School’s Headmaster in Taking Decision of Curriculum Development in The State Elementary School (SDN) 101786 Helvetia, Deli Serdang District - Nurtuah Tanjung; Nurika Khalila Daulay (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This study aims to describe the principal's leadership in decision-making curriculum development at Elementary School 101786 Helvetia Research includes principal leadership, decision-making, and curriculum development. This research uses qualitative research type with case study approach. The location of the research is Elementary School 101786 Helvetia District Labuhan Deli Deli Serdang Regency North Sumatra Province Source. The method according to the title of this study researchers using qualitative approach, the data in this study is, principals, teachers, school committee. The conclusions of this research are: 1. Leadership of principal in decision making of curriculum development at elementary school 101786 Helvetia "to make decision of curriculum development by making decision involving party, such as teacher, school committee, school supervisor, and decision making staff coordination meetings, in a participatory manner ".2. Leadership behavior, principals point to the style and strategy of a principal performing the principal's leadership task. Among the principal's effective leadership behaviors, although they still need to be improved for better, can be seen in the leadership style that always brings in coordination meetings with school committees, school supervisors, teachers and staff. 3. The principal's strategy in informing the decision-making result of curriculum development between headmaster and teacher is done directly in the form of face to face and indirectly in the form of telephone, sms, or letter.